Exploring the expression of DLL3 in gastroenteropancreatic neuroendocrine neoplasms and its potential diagnostic value - L. Yin; R. Wang; X. Ma; K. Jiang; Y. Hu; X. Zhao; L. Zhang; Z. Wang; T. Long; M. Lu; J. Li; Y. Sun (Scientific Reports)
Abstract Delta-like protein (DLL3) is a novel therapeutic target. DLL3 expression in gastroenteropancreatic neuroendocrine tumors (GEP-NECs) is poorly understood, complicating the distinction between well-differentiated neuroendocrine tumors G3 (NET G3) and poorly differentiated NEC. DLL3 immunohistochemistry (IHC) was performed on 248 primary GEP-NECs, correlating with clinicopathological parameters, NE markers, PD-L1, Ki67 index, and prognosis. Achaete-scute complex-like 1 (ASCL1) IHC was performed on some GEP-NECs. DLL3 IHC was conducted on 36 GEP-NETs, 29 gastric adenocarcinomas (GACs), and metastatic tumors (9 lymph node metastases and 19 distant metastases). DLL3 expression rates were 54.8% in GEP-NECs at the primary site, associated with small cell neuroendocrine carcinoma (SCNEC) (p < 0.001), chemotherapy before baseline (p = 0.015), and at least two NE markers (p = 0.048). DLL3 expression in metastatic GEP-NECs was similar to that of primary tumors. Expression rates in NET G1, NET G2, NET G3, and GACs were 0%, 0%, 15.8%, and 0%, respectively, highlighting DLL3 as a powerful tool for identifying poorly differentiated NEC. DLL3 expression was related to ASCL1 in GEP-NECs, especially in SCNEC. It was not correlated with progression-free survival (PFS) or overall survival(OS), regardless of cutoff value (1%, 50%, 75%). In conclusion, DLL3 targeted therapy may offer potential for the treatment of poorly differentiated NEC of the digestive system, although further studies are needed to validate its efficacy.